2021
DOI: 10.1177/22785337211015403
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Goods and Services Tax on Supply Chain Management

Abstract: Companies prefer to have their warehouses run in each state before goods and services tax (GST), but after GST whole supply chain phenomenon have changed. The purpose of this study is to address the impact of GST and then see how it affects the wider supply chain management sector. For this conceptual model is adapted and modified from Porter’s value chain model in current GST context. Online convenience sampling survey of 519 respondents from Indian companies which comprised eight different subsectors has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Government trade policies influence supply chain performance in different ways. According to Conceptually, Dhar and Khandelwal (2021) investigated how taxes affect supply chain performance, concentrating solely on the impact of service taxes and the moderating effects of the goods and services tax (GST) environment. Many of these studies have concentrated on developed countries and fast-growing economies.…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…Government trade policies influence supply chain performance in different ways. According to Conceptually, Dhar and Khandelwal (2021) investigated how taxes affect supply chain performance, concentrating solely on the impact of service taxes and the moderating effects of the goods and services tax (GST) environment. Many of these studies have concentrated on developed countries and fast-growing economies.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Many of these studies have concentrated on developed countries and fast-growing economies. For instance, Dhar and Khandelwal (2021) did a study in the UK. Further, Kasiewicz Kurklioski (2014) conducted a study in Poland focusing on the role of government policies on the supply chain performance of logistics companies.…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…GST has also significantly impacted the Indian supply chain recently, mainly on the truck transport logistics (Shokeen et al ., 2017). Studies have suggested that with the GST and the dismantling of state border checks, the truck turnaround has been reduced by 20% ( Dhar and Khandelwal, 2022).…”
Section: Introductionmentioning
confidence: 99%